Marine resource management and conservation in the Anthropocene - ASWANI, SHANKAR; BASURTO, XAVIER; FERSE, SEBASTIAN; GLASER, MARION; CAMPBELL, LISA; CINNER, JOSHUA E.; DALTON, TRACEY; JENKINS, LEKELIA D.; MILLER, MARC L.; POLLNAC, RICHARD; VACCARO, ISMAEL; CHRISTIE, PATRICK (Environmental conservation, 2018)
Because the Anthropocene by definition is an epoch during which environmental change is largely anthropogenic and driven by social, economic, psychological and political forces, environmental social scientists can effectively analyse human behaviour and knowledge systems in this context. In this subject review, we summarize key ways in which the environmental social sciences can better inform fisheries management policy and practice and marine conservation in the Anthropocene. We argue that environmental social scientists are particularly well positioned to synergize research to fill the gaps between: (1) local behaviours/needs/worldviews and marine resource management and biological conservation concerns; and (2) large-scale drivers of planetary environmental change (globalization, affluence, technological change, etc.) and local cognitive, socioeconomic, cultural and historical processes that shape human behaviour in the marine environment. To illustrate this, we synthesize the roles of various environmental social science disciplines in better understanding the interaction between humans and tropical marine ecosystems in developing nations where issues arising from human–coastal interactions are particularly pronounced. We focus on: (1) the application of the environmental social sciences in marine resource management and conservation; (2) the development of 'new' socially equitable marine conservation; (3) repopulating the seascape; (4) incorporating multi-scale dynamics of marine social–ecological systems; and (5) envisioning the future of marine resource management and conservation for producing policies and projects for comprehensive and successful resource management and conservation in the Anthropocene.